Understanding the role of sleep in suicide risk: qualitative interview study. Issue 8 (22nd August 2016) - Littlewood, Donna L; Gooding, Patricia; Kyle, Simon D; Pratt, Daniel; Peters, Sarah
Abstract : Objective: Sleep problems are associated with increased risk of suicide, independent of depression. This analysis explores narrative accounts of the role of sleep in relation to suicidal thoughts and behaviours. Design: Qualitative study, based on in-depth semistructured interviews which were analysed with an inductive, latent thematic analysis. Participants: A maximum variation sample of 18 people with experience of a major depressive episode, and suicidal thoughts and behaviours. Setting: Primary care, North West England. Results: Respondents emphasised the importance of sleep for recovery and management of their mental well-being. Moreover, three inter-related pathways were identified, whereby beliefs about sleep contributed to suicidal thoughts and behaviours. First, being awake during the biological night heightened risk of suicidal behaviours, as this was perceived to be an opportune time for a suicide attempt due to the decreased chances that a friend of family member would intervene during a suicide attempt. Additionally, the reduction in available support at night added to suicide risk. Second, failure to achieve good sleep was perceived to make life harder through contributing to core features of depression, such as negative thinking, attention difficulties and inactivity. Third, sleep acted as an alternative to suicide, by providing an escape from problems, including mental health problems, in waking life. However, this desire to sleep to escape was associated with excessive daytime sleeping, which subsequently may reinforce disturbed sleeping patterns. Conclusions: Sleep problems should be an important treatment target when working with suicidal clients. More broadly, night-time service provision should be considered when developing suicide prevention initiatives.